Effect of starch and fibre on faba bean protein gel characteristics. (October 2022) - Johansson, Mathias; Johansson, Daniel; Ström, Anna; Rydén, Jesper; Nilsson, Klara; Karlsson, Jakob; Moriana, Rosana; Langton, Maud
Abstract: Faba bean is a promising alternative to soybean for production of protein-rich plant-based foods. Increased understanding of the gelling behaviour of non-soy legumes can facilitate development of novel plant-based foods based on other legumes, such as faba bean. A mixture design was used in this study to evaluate the effect of different proportions of protein, starch and fibre fractions extracted from faba beans on gelation properties, texture and microstructure of the resulting gels. Large deformation properties, in terms of fracture stress and fracture strain, decreased as fibre and/or starch replaced protein. In contrast, Young's modulus and storage modulus increased with substitution of the protein. Light microscopy revealed that for all gels, protein remained the continuous phase within the region studied (65–100% protein fraction, 0–35% starch fraction, 0–10% fibre fraction in total flour added). Swollen and deformed starch granules were distributed throughout the mixed gels with added starch. Leaked amylose aggregated on starch and fibre surfaces and in small cavities (<1 μm) throughout the protein network. No clear difference between samples in protein network structure was observed by scanning electron microscopy. The reduction in large deformation properties was tentatively attributed to inhomogeneities created by the added starch and fibre. The increase in small deformation properties was hypothesised to be affected by water adsorption and moisture stability through the starch and fibre, increasing the effective protein concentration in the surrounding matrix and enhancing the protein network, or potentially by starch granules and fibre particles acting as active fillers reinforcing the gel structure. Graphical abstract: Image 1 Highlights: Partly replacing protein with starch and/or fibre reduce the fracture stress. Partly replacing protein with starch and/or fibre increase the storage modulus. Addition of starch and/or fibre did not largely alter the protein network structure.